Large segmental radius and ulna defect treated by bone transportation with the Ilizarov technique - Rahal, Sheila Canevese [UNESP]; Volpi, R. S.; Vulcano, Luiz Carlos [UNESP]; Ciani, R. B.; Mannarino, R. (Australian Veterinary Assn, 2003)
An 8-year-old male Boxer with a severely contaminated open fracture of the left radius and ulna fracture, produced by a helicopter propeller, was treated using bone transport by the Ilizarov method. Extensive diaphyseal bone loss and soft-tissue vascular damage were present. The radius and ulna were stabilised with an Ilizarov ring external fixator. The bone defect was partially shortened and restored by gradual transport of a bone segment created from proximal segments of the radius and ulna. The external fixator was removed 4fi months after the beginning of the latency period, due to instability caused by osteolysis around the wires. A cast was placed for 3 weeks. Although the bone transport had resulted in formation of approximately 4 cm of bone, the antebrachium showed approximately 50% shortening when compared to the contralateral limb. The infection was eradicated, and the dog was able to bear weight on the operated limb when walking.